Cost of Severe Chronic Obstructive Pulmonary Disease Exacerbations in a High Burden Region in North India - Parvaiz A. Koul; Aqsa Amin Nowshehr; Umar H. Khan; Rafi A. Jan; S. U. Shah (Ubiquity Press, 2019)
Background: Data on costs of acute exacerbations of COPD (AECOPD) in low-income countries are sparse. We conducted a prospective survey to assess direct and indirect costs of severe AECOPD in a tertiary care setting in a high prevalence area of North India. Methods: We conducted face-to-face surveys using a semi-structured questionnaire among a convenience sample of 129 consenting patients admitted with AECOPD. Data were collected on out-of-pocket costs of hospitalization, consultation, medications, diagnostics, transportation, lodging, and missed work days for self and their attendants. Out-of-pocket costs were supplemented with World Health Organization-CHOICE estimates. Missed work-days were valued on per capita national income (Indian Rupees [INR] 68,748, US$1,145.8). Median total cost per exacerbation episode was INR 44,390 (Inter-quartile range [IQR]: INR 33,354-63,642; US$739.8, IQR: 555.9-1060.7). Hospital costs constituted the largest component of the costs (71%) followed by other costs directly borne by the patient himself (29%), medicine costs (14%), transportation charges (2%) and diagnostic tests (3%). Indirect costs to caregivers (median INR 1,544, IQR: INR 0-17,370 INR; US$25.7, IQR: US$0-289.5), calculated as financial loss due to missed work days, accounted for 4% of the total cost. Expenses were covered by family members in all but 11 patients. Conclusions: AECOPD in India are associated with substantial costs and strategies to reduce the burden of disease such as smoking cessation, influenza and pneumococcal vaccination, etc should be aggressively pursued.